40 Novel Genomic Regions Associated with Igg Antibody Response to PRRSV Vaccination Revealed by Haplotype-based GWAS. (7th May 2021) - Sanglard, Leticia P; Huang, Yijian; Gray, Kent A; Linhares, Daniel; Dekkers, Jack C; niederwerder, Megan; Fernando, Rohan; Serão, Nick V
Abstract: Previous studies on genomics of antibody response, measured as sample-to-positive (S/P) ratio, to Porcine Reproductive and Respiratory Syndrome virus (PRRSV) have reported a major quantitative trait locus (QTL) on the major histocompatibility complex (MHC) on chromosome 7, explaining ~25% of the genetic variance of this trait. S/P ratio following modified live PRRSV vaccination in crossbred commercial gilts has been proposed as genetic indicator for reproductive performance in non-infected purebred sows and PRRSV-vaccinated crossbred sows. This motivated further genomic study for this trait by performing haplotype-based genome-wide association study (GWAS). 906 naïve F1 (Landrace x Large White) had blood samples taken at ~50d after vaccination for measuring PRRSV ELISA S/P ratio and genotyping. Haplotype-based GWAS identified 8 genomic regions on chromosomes 4 (108 Mb), 7 (15, 21, and 24–27 Mb), and 9 (33 Mb) that were associated (q-value < 0.07) with S/P ratio. From those, only the MHC region (chromosome 7; 24 – 26 Mb) had been identified in the SNP based GWAS. The main SNP identified in the SNP based GWAS (H3GA0020505) was not in LD with the haplotype; thus, we added this SNP to the haplotype model. We observed that the haplotype explained more of the genetic variance compared to the H3GA0020505 SNP, indicating that the MHC haplotype is in stronger LD with the QTL than the H3GA0020505 SNP. All the significant regions associated with S/P ratio included immune-related candidate genes, such as SLA-DOB, TAP2, TAPBP, TMIGD3, and ADORA. This study validated the QTL identified on the MHC region, narrowing the search for causal genes in this region, and identified new genomic regions, along with candidate genes associated with S/P ratio. Identifying novel genomic regions provides more resources for marker-assisted selection and genomic prediction of S/P ratio in purebred and commercial pig populations.